Inferior and Superior Analysis of the Main Character of Cerkak “Sendhang ing Pangangene Barji” by Irul S. Budianto: Psychological Study of Alfred Adler - Febriyola, Sheila Marta; Clarenita, Ananda (Abjad Journal of Humanities & Education, 2023)
This research analyses the inferior and superior forms of the main characters in the story “Sendhang Ing Pangangene Barji”. This study used a descriptive qualitative method. This research uses Alfred Adler's psychology approach theory. The data in this research is in the form of text quotations that describe the feelings of inferiority and superiority of the main character in the story "Sendhang Ing Pangangene Barji". The data source in this research is the story "Sendhang Ing Pangangene Barji" by Irul S. Budianto, which is contained in the Jayabaya magazine, Sunday third-edition January 2019. The data collection technique in this research uses library study techniques. The data analysis technique in this research uses description techniques. The inferior form shown by the main character in the story "Sendhang Ing Pangangene Barji" is in the form of feelings of confusion and despair. In achieving success and superiority, the main character needs support from other characters. This support takes the form of advice. This advice ultimately makes the character succeed, namely the emergence of feelings of confidence and enthusiasm to continue life after despairing at the severity of the problems faced previously.